O impacto da legalização das apostas esportivas no brasil: uma análise dos aspectos criminais no contexto do direito penal brasileiro - Pinto, Mauro Oliveira de Melo (2024)
In 2023, Law No. 14,790/2023 (Brazil) was enacted, regulating sports betting in Brazilian territory. Thus, the present study addresses the impact of the legalization of sports betting in Brazil when analyzed from the criminal aspects within the context of Brazilian criminal law, in order to discuss the impact of the legalization of sports betting in Brazil from the perspective of Brazilian criminal law. To this end, it was necessary to research the historical context involving sports betting and the criminalization of gambling in Brazil, analyze from a criminal perspective what the impact of legalization is on combating match-fixing in Brazilian football, and identify the repercussions that the legalization of sports betting has on criminal legislation. To achieve this purpose, research was conducted using the deductive method, with a qualitative approach, utilizing the technical procedure of bibliographic research. In this context, it was found that gambling practices, despite being illegal, are deeply embedded in Brazilian culture. Therefore, it was observed that the criminalization of gambling is still related to prejudice disguised as morality. Thus, it is expected that with the legalization of betting, a new precedent will be set for the possibility of decriminalizing gambling. Moreover, it was found that match-fixing is the main adversity brought about by the legalization of sports betting. In this regard, the context of Brazilian football emerges as one of the main places for the existence of match-fixing and crimes involving the theme. Furthermore, with the study of the repercussions that the legalization of sports betting has on criminal legislation, it is possible to analyze the criminal types involved in the theme. As a result, it was found that there is still much to discuss regarding sports corruption offenses, considering that there is a divergence among authors about which conduct constitutes a crime; additionally, it was identified that legalization also brings significant challenges to combating money laundering offenses due to the large financial transactions involved in the market. Based on the above, it was possible to conclude that the legalization of sports betting brings a series of implications and challenges to Brazilian criminal law, such as the need to discuss the archaic criminalization of gambling and the necessity for more efficient policies to combat match-fixing and money laundering.